Physicians' views on patient participation in choice of oral anticoagulants in atrial fibrillation-a qualitative study - Aarnio E; Huupponen R; Hämeen-Anttila K; Merikoski M; Puhakka J; Korhonen MJ (Wiley, 2022)
Direct oral anticoagulants provide an alternative to vitamin K antagonists for the anticoagulation therapy in atrial fibrillation (AF). The availability of several treatment options with different attributes makes shared decision-making appropriate for the choice of anticoagulation therapy. The aim of this study was to understand how physicians choose an oral anticoagulant (OAC) for patients with AF and how physicians view patients' participation in this decision. Semi-structured interviews with 17 Finnish physicians (eight general practitioners and nine specialists) working in the public sector were conducted. An interview guide on experience, prescribing and opinions about oral anticoagulants was developed based on previous literature. The data were thematically analysed using deductive and inductive approaches. Based on the interviews, patient's opinion was the most influential factor in decision-making when there were no clinical factors limiting the choice between OACs. Of patient's preferences, the most important was the attitude towards co-payments of OACs. Patients' opinions on monitoring of treatment, dosing and antidote availability were also mentioned by the interviewees. The choice of an OAC in AF was patient-centred as all interviewees expressed that patient's opinion affects the choice.